(untitled) (World Economics and Finance Bulletin, 2026)
This study examines the impact of flexible pricing on sales volume and profit margins in the FMCG sector. The research focuses on analyzing how adaptive pricing strategies influence consumer demand, revenue generation, and marginal profitability under competitive market conditions. Using econometric and comparative analysis methods, the study evaluates the relationship between pricing flexibility, demand elasticity, and business performance indicators. The findings reveal that flexible pricing significantly increases sales volume, improves inventory turnover, and enhances profit margins compared to traditional static pricing approaches. The results also demonstrate that the effectiveness of flexible pricing largely depends on digital infrastructure, realtime data analysis, and strategic pricing management. Furthermore, the study proposes a hybrid pricing model that combines stable base pricing with dynamic promotional adjustments in order to balance profitability and market competitiveness. The research provides practical recommendations for enterprises seeking to optimize pricing strategies and improve operational efficiency in rapidly changing market environments.